2019
DOI: 10.1038/s41598-019-41104-5
|View full text |Cite
|
Sign up to set email alerts
|

Linking social preferences and ocean acidification impacts in mussel aquaculture

Abstract: Ocean Acidification (OA) has become one of the most studied global stressors in marine science during the last fifteen years. Despite the variety of studies on the biological effects of OA with marine commercial species, estimations of these impacts over consumers’ preferences have not been studied in detail, compromising our ability to undertake an assessment of market and economic impacts resulting from OA at local scales. Here, we use a novel and interdisciplinary approach to fill this gap. We experimentall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…Consequently, there may be the risk of a significant decrease in the meat quality of black sea bream from the end of the 21st century. Studying the impact of OA on mussels, Martin et al [ 57 ] reported a negative effect on meat quality. Furthermore, the studies of Rossoll et al [ 58 ] and Jin et al [ 59 ] also reported a decrease in fish samples’ meat quality due to OA.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, there may be the risk of a significant decrease in the meat quality of black sea bream from the end of the 21st century. Studying the impact of OA on mussels, Martin et al [ 57 ] reported a negative effect on meat quality. Furthermore, the studies of Rossoll et al [ 58 ] and Jin et al [ 59 ] also reported a decrease in fish samples’ meat quality due to OA.…”
Section: Discussionmentioning
confidence: 99%
“…When it comes to ocean acidification effects, molluscs and crustaceans are of particular interest, as their likely responses are relevant to human nutrition, food security, and livelihoods (San Martin et al, 2019). The level of understanding has greatly improved across these commercially important shellfish groups (Browman, 2016), and evidence is strong that marine calcifiers, dependent upon calcium carbonate (CaCO 3 ) to create shells or skeletons, are under direct threat from ocean acidification across all life stages (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A large body of evidence is available on the negative impacts of projected OA on the survival, growth, calcification, immune responses, and reproduction of marine organisms. Only recently, however, have a very small number of experimental studies attempted to estimate the possible socio-economic consequences of OA acidification due to the altered quality of seafood 5 7 . One notable such study revealed that culturing shrimp in acidified seawater negatively affected their flavor 5 .…”
Section: Introductionmentioning
confidence: 99%
“…As such, the concentrations and relative proportions of amino acids in shrimp and other seafood can have important repercussions for consumers and seafood producers. San Martin et al 7 developed a model to test how OA could impact on the taste of seafood and its appeal to consumers. They found that the attributes of mussels that are affected by OA also tend to determine consumers’ preferences and that people would only be prepared to buy mussels affected by OA if they were 52% cheaper than they are at present.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation